DAYA TERIMA DAN KANDUNGAN GIZI YOGURT SUSU PASTEURISASI DENGAN SUBSTITUSI PANGAN LOKAL SARI LABUKUNING (Cucurbita Moschata) DAN SARI JAMBU HUTAN (Bellucia pentamera naudin) SEBAGAI MINUMAN PROBIOTIK - Yulianti; Dahliansyah; Nopriantini (Jurusan Gizi Poltekkes Pontianak, 2025)
Lactobacillus bulgaricus and Streptococcus thermopillus bacteria ferment milk to produce yogurt. Innovation in making yogurt from local foods like yellow pumpkin (Cucurbita moschata) and forest guava (Bellucia pentamera Naudin) can increase the acceptance and nutritional content of yogurt as a probiotic drink. The goal is to find out if pasteurized milk yogurt that is mixed with yellow pumpkin juice (Cucurbita moschata) and wild guava juice (Bellucia pentamera Naudin) as probiotic drinks is acceptable and what kind of nutrients it has. This method employs experimental research involving three formulations (F1, F2, and F3). The test was carried out in 3 stages, namely organoleptic testing of 25 panellists to determine the panellists' acceptability of color, aroma, taste, texture, and consistency, an effectiveness index test, and the nutritional content of carbohydrates, protein, fat, water, and ash, which were carried out on yogurt. The study's results revealed that the third formulation (F3), which included pasteurized milk (175 ml), yellow pumpkin juice (55 ml), forest guava juice (60 ml), sugar (10 g), and starter (10 ml), achieved the best value of the organoleptic effectiveness index. This formulation had a carbohydrate content of 9.02%, fat 2.78%, protein 2.01%, fiber 0.00%, ash 0.58%, and 85.59% water. The conclusion of the study shows local food substitutions of pumpkin juice (Cucurbita moschata) and forest guava juice (Bellucia pentamera naudin) do not affect the color, aroma, taste, texture, and consistency of pasteurized milk yogurt as a probiotic drink. Keywords: Yoghurt, pasteurized milk, pumpkin juice, forest guava juice, probiotics. Details: 1) Main researcher; 2) Main supervisor; 3) Assistant supervisor